The Effect of the Donor’s and Recipient’s Sex on Red Blood Cells Evaluated Using Transfusion Simulations - Emmanuel Laengst; David Crettaz; Jean-Daniel Tissot; Michel Prudent (Cells, 2023)
The hypothesis of the potential impact of the sex of red blood cell (RBC) concentrate (RCC) donors, as well as the sex of the recipients, on the clinical outcome, is still under evaluation. Here, we have evaluated the sex impact on RBC properties using in vitro transfusion models. Using a “flask model”, RBCs from RCCs (representing the donor)—at different storage lengths—were incubated in a sex-matched and sex-mismatched manner with fresh frozen plasma pools (representing the recipient) at 37 °C, with 5% of CO2 up to 48 h. Standard blood parameters, hemolysis, intracellular ATP, extracellular glucose and lactate were quantified during incubation. Additionally, a “plate model”, coupling hemolysis analysis and morphological study, was carried out in similar conditions in 96-well plates. In both models, RBCs from both sexes hemolyzed significantly less in female-derived plasma. No metabolic or morphological differences were observed between sex-matched and -mismatched conditions, even though ATP was higher in female-derived RBCs during incubations. Female plasma reduced hemolysis of female- as well as male-derived RBCs, which may be related to a sex-dependent plasma composition and/or sex-related intrinsic RBC properties.